Treatment outcomes in a rural HIV clinic in South Africa: Implications for health care - Olufemi B. Omole; Mary-Anne M.L. Semenya (AOSIS, 2016)
Objective: To assess the treatment outcomes of an HIV clinic in rural Limpopo province, South Africa. Methods: A retrospective cohort study involving medical records review of HIV-positive patients initiated on antiretroviral treatment (ART) was conducted from December 2007 to November 2008 at Letaba Hospital. Data on socio-demographic characteristics, CD4 counts, viral loads (VLs), opportunistic infections, adverse effects of treatment, hospital admissions, and patient retention at 6, 12, 24, and 36 months on ART were collected. Analysis included descriptive statistics, chi-square and t-tests. Results: Of 124 patient records sampled, the majority of patients were female (69%), single (49%), unemployed (56%), living at least 10 km from the hospital (52.4%), and were on treatment at 36 months (69%). Approximately 84% of patients achieved viral suppression (VLs < 400 copies/mL) by 6 months of ART and the mean CD4 count increased from 128 at baseline to 470 cells/mm3 at 24 months. There was a mean weight gain of 5.9 kg over the 36 months and the proportion of patients with opportunistic infections decreased from 54.8% (n = 68) at baseline to 15.3% (n = 19) at 36 months. Although the largest improvements in CD4, VLs, and weights were recorded in the first 6 months of ART, viral rebound became evident thereafter. Of all variables, only age < 50 years and being pregnant were significantly associated with higher VLs (p = 0.03). Conclusion: Good treatment outcomes are achievable in a rural South African ART clinic. However, early viral rebound and higher VLs in pregnancy highlight the need for enhanced treatment adherence support, especially for pregnant women to reduce the risk of mother to child transmission. Keywords: CD4 count; viral load; rura;, treatment outcomes; antiretroviral treatment; patient retention